Jesus and Muhammad: parallel tracks, parallel lives - Peters, Francis E. (Oxford University Press, 2011)
Clearing the ground -- The settings -- Opening the files -- The critic at work: coming of age -- The living voice -- The message: Jesus in Galilee -- The message: Muhammad at Mecca -- Act II: tragedy and triumph -- A new dawn: the aftermath, the legacy -- Epilogue: spreading the word